Covenant and Pax Deorum: Polyvalent Prodigies in Josephus’ Jewish War - Davies, Jonathan (Histos, 2019)
This paper considers the question of culturally-directed doublespeak in Josephus’ Jewish War, of the possibility of Josephus sending different messages to Gentile and Jewish readers in the same text. It offers two readings of a passage in Jewish War 6 which describes the portents which prefigure the destruction of the Jerusalem Temple, and explores how Josephus expresses his narrative in a way which simultaneously evokes parallels with both Roman religion and biblical prophecy and historiography, resulting in a passage which resonates radically differently depending on the parallels which the reader can bring to bear, and which inverts the cultural power-dynamic of Roman imperialism by offering greater interpretative power to those readers who come from an unprivileged provincial culture. It offers a fruitful approach to considering an author who is marked above all by hybridity, and by a mastery of more than one literary tradition.